A highly conserved repeated chromosomal sequence in the radioresistant bacterium Deinococcus radiodurans SARK. - Lennon, E (1991)
A DNA fragment containing a portion of a DNA damage-inducible gene from Deinococcus radiodurans SARK hybridized to numerous fragments of SARK genomic DNA because of a highly conserved repetitive chromosomal element. The element is of variable length, ranging from 150 to 192 bp, depending on the absence or presence of one or two 21-bp sequences located internally. A putative translational start site of the damage-inducible gene is within the reiterated element. The element contains dyad symmetries that suggest modes of transcriptional and/or translational control.